2018
DOI: 10.3389/fpsyg.2018.00821
|View full text |Cite
|
Sign up to set email alerts
|

Who Benefits From Humor-Based Positive Psychology Interventions? The Moderating Effects of Personality Traits and Sense of Humor

Abstract: The evidence for the effectiveness of humor-based positive psychology interventions (PPIs; i.e., interventions aimed at enhancing happiness and lowering depressive symptoms) is steadily increasing. However, little is known about who benefits most from them. We aim at narrowing this gap by examining whether personality traits and sense of humor moderate the long-term effects of humor-based interventions on happiness and depressive symptoms. We conducted two placebo-controlled online-intervention studies testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 59 publications
2
39
0
1
Order By: Relevance
“…Whereas the beneficial effects of humour are produced by virtue of the cognitive shifts that it entails and the changes in affective quality that accompany it. In other words, it will be influenced by many factors such as cognitive function and personal traits (Dixon, 1980;Wellenzohn, Proyer, & Ruch, 2018). Some studies (Bozikas et al, 2007;Parnowska, Braniecka, & Radomska, 2013) indicated low reception of humour in schizophrenia does a negative impact on the effectiveness of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the beneficial effects of humour are produced by virtue of the cognitive shifts that it entails and the changes in affective quality that accompany it. In other words, it will be influenced by many factors such as cognitive function and personal traits (Dixon, 1980;Wellenzohn, Proyer, & Ruch, 2018). Some studies (Bozikas et al, 2007;Parnowska, Braniecka, & Radomska, 2013) indicated low reception of humour in schizophrenia does a negative impact on the effectiveness of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This conception of adolescence is currently fairly different for studies do not only describe the adolescent as a source of problems but also as a valuable asset in a development process [3,4]. This change took place with the arrival of positive psychology, as one of its objectives is to promote psychological research and practice in such areas as positive traits (strengths), positive emotions, and their contribution to well-being [5].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the field is being more thoughtfully defined to encompass the variation of possible outcomes of interventions. The effectiveness of interventions delivered electronically has been studied (e.g., Wellenzohn et al, 2018), cross-culturally (Flores & Lee, 2019), and clinically (Chakhssi, Kraiss, Sommers-Spijkerman, & Bohlmeijer, 2018). Positive education, or the implementation of positive psychology interventions into schooling, has also been studied (Seligman, Ernst, Gillham, Reivich, & Linkins, 2009).…”
mentioning
confidence: 99%